Утицај антиоксидативних дијета, нутрацеутика и интервенција физичке активности на превенцију кардиометаболичких болести: преглед - Parekh, Neel; Merota, Vipina; Joshi, Ruchira; Kaur, Ginpreet; Tuli, Hardeep S; Buttar, Harpal S (Scripta Medica, 2023)
Hippocrates – Father of Medicine (ca 460-370 B.C.) – endorsed the curative effects of foods; he said: “Leave your drugs in the chemist’s pot if you can heal the patient with food”. This review focuses on the management of cardiometabolic diseases (CMDs) with nutraceuticals and antioxidant diets such as Allium sativum, turmeric, soybean, peptides, phytosterols, resveratrol, polyphenolic substances etc. CMDs are a cluster of conditions linked to altered fat and carbohydrate metabolism as well as macro- and micro-vascular problems. CMDs cause severe pathophysiological and metabolic alterations in the body, resulting in the occurrence of chronic diseases like atherosclerosis, coronary heart disease and stroke, neurodegenerative ailments, fatty liver, kidney malfunction, hypercholesterolaemia, hyperlipidaemia, insulin resistance and some cancers, consequently imposing a very high economic burden on the healthcare costs. Currently used pharmacotherapies are not only expensive but also are associated with undesirable adverse events. Thus, there is an urgent need for affordable, cost-effective and alternative safe therapies for the prevention and management of CMDs. Holistic approaches targeted for health promotion and prevention of CMDs include the intake of antioxidant-rich diets, anti-inflammation wholesome foods and moderate physical activity (about 30 min/day). Such strategies will not only prevent obesity-related CMDs, type 2 diabetes mellitus (T2DM), coronary heart disease and stroke, but also will improve the quality of patient’s life and consequently reduce healthcare burdens. Nutraceuticals and probiotics exhibit anti-inflammation, anti-aging, anti-obesity and anti-diabetic effects, thereby reducing the adverse health risks associated with CMDs. Antioxidants protect cell membranes and DNA from excessive free radicals, which contribute to CMD related diseases. Physical exercise along with dietary interventions helps to mitigate oxidative stress, improve blood triglyceride levels, increase HDL-cholesterol and reduce LDL-cholesterol and reverse the biological markers associated with CMDs. Many studies have provided robust scientific evidence and demonstrated links between dietary interventions, nutraceuticals, probiotics, wholesome foods and physical activity for the prevention of CMDs. The major limitations in promoting nonpharmacological therapies for health and well-being benefits are a lack of public awareness and a paucity of clinical nutrition instruction for medical students on the merits of complementary methods for the prevention and management of CMDs. The goals of this review are to provide up-to-date knowledge about selected nutraceuticals, wholesome foods and physical activity in the prevention of CMDs and the underlying mechanisms associated with each intervention, which will ultimately improve patient’s quality of life and assist in reducing healthcare costs globally.